Interaction of mammalian mitochondrial elongation factor EF-Tu with guanine nucleotides. - Cai, Y. C. (Cold Spring Harbor Laboratory Press, 2000)
Elongation factor Tu (EF-Tu) promotes the binding of aminoacyl-tRNA (aa-tRNA) to the acceptor site of the ribosome. During the elongation cycle, EF-Tu interacts with guanine nucleotides, aa-tRNA and its nucleotide exchange factor (EF-Ts). Quantitative determination of the equilibrium dissociation constants that govern the interactions of mammalian mitochondrial EF-Tu (EF-Tu(mt)) with guanine nucleotides was the focus of the work reported here. Equilibrium dialysis with [3H]GDP was used to measure the equilibrium dissociation constant of the EF-Tu(mt) x GDP complex (K(GDP) = 1.0 +/- 0.1 microM). Competition of GTP with a fluorescent derivative of GDP (mantGDP) for binding to EF-Tu(mt) was used to measure the dissociation constant of the EF-Tu(mt) x GTP complex (K(GTP) = 18 +/- 9 microM). The analysis of these data required information on the dissociation constant of the EF-Tu(mt) x mantGDP complex (K(mGDP) = 2.0 +/- 0.5 microM), which was measured by equilibrium dialysis. Both K(GDP) and K(GTP) for EF-Tu(mt) are quite different (about two orders of magnitude higher) than the dissociation constants of the corresponding complexes formed by Escherichia coli EF-Tu. The forward and reverse rate constants for the association and dissociation of the EF-Tu(mt) x GDP complex were determined using the change in the fluorescence of mantGDP upon interaction with EF-Tu(mt). These values are in agreement with a simple equilibrium binding interaction between EF-Tu(mt) and GDP. The results obtained are discussed in terms of the recently described crystal structure of the EF-Tu(mt) x GDP complex.